Hyperthermia following traumatic brain injury: a critical evaluation - Hilaire J Thompson; Nancy C Tkacs; Kathryn E Saatman; Ramesh Raghupathi; Tracy K McIntosh (Neurobiology of Disease, 2003)
Hyperthermia, frequently seen in patients following traumatic brain injury (TBI), may be due to posttraumatic cerebral inflammation, direct hypothalamic damage, or secondary infection resulting in fever. Regardless of the underlying cause, hyperthermia increases metabolic expenditure, glutamate release, and neutrophil activity to levels higher than those occurring in the normothermic brain-injured patient. This synergism may further compromise the injured brain, enhancing the vulnerability to secondary pathogenic events, thereby exacerbating neuronal damage. Although rigorous control of normal body temperature is the current standard of care for the brain-injured patient, patient management strategies currently available are often suboptimal and may be contraindicated. This article represents a compendium of published work regarding the state of knowledge of the relationship between hyperthermia and TBI, as well as a critical examination of current management strategies.